Effect of oil palm compost and sandy soil on the growth of cacao (Theobroma cacao L.) seedlings - Oscar A. Tuesta; Juan C. Tuesta; Robert Rafael-Rutte; Enrique Arévalo-Gardini; Juan M. Vela L.; Cesar O. Arévalo-Hernández (Agronomía Mesoamericana)
Introduction. Low-fertility soils and high logistics costs for seedling production characterize the Peruvian Amazon. Objective. To evaluate the effect of a combination of sandy soil and oil palm compost on substrate, growth, and nutrition of cocoa seedlings under greenhouse conditions. Materials and methods. The experiment was conducted for 90 days in Yurimaguas, Loreto, using a completely randomized design in a 5 • 5 matrix, with five doses of oil palm compost and sandy soil to determine the best combination for cocoa growth and nutrition. Height (cm), diameter (mm), leaf area (cm2), dry weight of stem and root were measured; soil chemical analysis and plant analysis (macro and micronutrients) were also conducted. Results. Sandy soil showed no significant effect on cocoa seedlings, while treatments with oil palm compost promoted shoot and root biomass. Additionally, this compost favored conditions for seedling growth by promoting higher organic matter, available phosphorus, exchangeable calcium, potassium, and higher cation exchange capacity. Regarding cocoa nutrition, it promoted greater absorption of macro and micronutrients in seedlings. Conclusions. These results indicate that the best treatment was the one composed entirely of oil palm compost, as it promotes growth and nutrition by improving substrate conditions.